The Role of Teachers in Improving Qur’anic Reading and Writing Skills with Proper Makharijul Huruf and Fostering Love for Worship among Students in Rengas Pulau Subdistrict - Syahrin Mubarak Lubis (Integrasi: Jurnal Studi Islam dan Humaniora, 2026)
This study aims to analyze the role of teachers in improving Qur’anic reading and writing skills with proper makharijul huruf and fostering students’ love for worship in Rengas Pulau Subdistrict. The ability to read and write the Qur’an correctly is a fundamental aspect of Islamic education, as it influences students’ understanding of religious teachings and the development of religious character. This research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews with teachers and students, and documentation. The findings indicate that teachers play a strategic role as educators, mentors, motivators, and role models in Qur’anic literacy learning. The implementation of talaqqi, tahsin, habituation, and exemplary practices was found to be effective in improving the accuracy of makharijul huruf and fostering students’ love for worship. The study concludes that professional and consistent teacher involvement significantly contributes to enhancing Qur’anic literacy and worship habits among students.